Philological Notes on the Letter lambda in a New Greek-English Dictionary. I. λαβάργυρος – λάσθη - Olson, S. Douglas (Hyperboreus, 2023)
Two generations ago, Robert Renehan published a series of articles expanding, reﬁning, and correcting entries in the 9th edition of the monumental Liddell–Scott–Jones Greek-English Lexicon (1940) as supplemented by Barber and his fellow editors (1968). These notes on the letter lambda in the new Brill Dictionary of Ancient Greek are oﬀered in a similar spirit.